Evaluasi Pasar Tradisional: Studi Kasus Pasar Rakyat Krueng Mane - Novianti, Yenny; Aini, Nur; Fahrizal, Effan (Arsir, 2023)
The Krueng Mane People's Market is one of the traditional markets built by the government. Traditional markets are part of the economic facilities and infrastructure in Indonesia. However, its existence is increasingly being eroded by the modern market and the less than optimal use. The government has launched a Market Revitalization Program, but many have failed. The purpose of this study was to determine the use and design criteria of the functional aspects of standard elements of space, accessibility, zoning and facilities. This study uses an evaluation method with a qualitative descriptive elaboration. In collecting data, the method used is place centered mapping on field observations, surveys using questionnaires and interviews. The results of the study indicate that the aspects studied have not been effective for use by traders and buyers during their inhabited period. Therefore, it is suggested that the design criteria are the size of the trading room based on the standard, the width of the circulation does not vary in the sense that it must comply with the standard, the zoning should be given a clear marker and the facilities for the market must be provided again so that the market that has been built can be used optimally in the future.